Awareness Regarding Patient Rights among Hospitalized Patients in a Hospital of Rupandehi - Gurung, Saraj; Sapkota, Ritika (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Patients' rights is recently introduced term in health sciences literature and practice and has become an important part of modern health care practice. Patients now are much more aware of what they expect from health care professionals, when they enter the health care environment. The aim of the study was to find out the knowledge regarding patient rights among hospitalized patients. MATERIAL AND METHODS: Descriptive study was conducted to find out the knowledge regarding patients' rights among hospitalized patients. Seventy two respondents were selected by using convenience sampling technique. Semi-structured interview schedule was used to collect the data and collected data were analyzed by using descriptive statistics with Statistical Package for Social Science software (SPSS) version 20. RESULTS: The findings of the study revealed that 59.72% of the respondents had high knowledge regarding patient rights. Cent percent of the respondents had knowledge that being treated with respect, equitable treatment, decide to participate in human experiment are patient rights. Ninety three percent, 92% and 31.90% respondents had knowledge that right to informed consent, right to confidentiality, right to privacy and right to leave against medical advice are patients' rights respectively. CONCLUSION: Based on the findings of the study, it is concluded that nearly three fourth of the respondents have high knowledge regarding patients' rights. It is recommended that management of hospital should conduct orientation program regarding human rights to health care providers to deliver health care in human right aspect.